Star Shine Kindergarten and Nursery / Sitti Nadirah Mohd. Salleh ..[et al.] - Mohd. Salleh, Sitti Nadirah; Frendius, Syanley G.; Muhammad Noh, Nurain; Ramlee, Dayang Fadzilliah; Osman, Nur Anis (2011)
Business can make us get easier profit but we must prepare it carefully and brilliantly. It is alright if the first business that you held did not gain profit. This is because it was the first time you go trough on business. It is also happen with us. All of us are trying to involve ourselves in business world. Our business is a partnership business and we would like to open a kindergarten and a nursery. First of all we want to introduce you to our company that called as Star Shine Kindergarten. This business is combining the nursery and kindergarten. Our business is more focused on services and will be located at Taman Mega, Jalan Labuk, 90000, Sandakan, Sabah. The reason we choose this place because it is situated at the housing lot and busy area. Most of the family there are the person that has a carrier. They do not have enough time to look after their child. So, we take an initiative to build the kindergarten and nursery there to help the parents to take care and teach them. However, our business commencement is still in the process of registration. In addition, the factors of selecting the proposed business because we care about the children’s education and we want to born the children that has many creativity, active and full of skills for their selves, family and country. Besides that, we also try to avoid them from being hurt with their babysitters. In the future, we hopefully that our business will born many useful person that can help to develop our country.